To pass or not to pass: A mathematical model for competitive interactions in Rugby Union - Diniz, A.; Barreiros, J.; Passos, P. (Journal of Motor Behavior, 2014)
The authors` aim was to investigate the speed-accuracy tradeoff in soccer kicking with the dominant and nondominant foot by using different types of instructions prioritizing speed or accuracy in experienced soccer players. Ten male soccer players were randomly given 1 of the 4 instructions that differed in aspects of the kick they should emphasize and what the secondary aim would be (speed or accuracy). It was found that ball velocity was affected by instruction in the expected way: emphasis on accuracy and ball velocity reduced for both kicking feet. In addition kicking accuracy increased when emphasizing this, but only with the dominant foot indicating that Fitts` law only was found in kicks with the dominant foot.